Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.3 - Adding and Subtracting Rational Expressions with the Same Denominator and Least Common Denominator - Exercise Set: 31

Answer

LCD=(x-1)(x+1)(2x+1)(3x+1)

Work Step by Step

$\frac{2x}{3x^{2}+4x+1}$, $\frac{7}{2x^{2}-x-1}$ 3$x^{2}$+4x+1=3$x^{2}$+x+3x+1=x(3x+1)+1(3x+1)=(x+1)(3x+1) 2$x^{2}$-x-1=2$x^{2}$+x-2x-1=x(2x+1)-1(2x+1)=(x-1)(2x+1) LCD=(x-1)(x+1)(2x+1)(3x+1)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.